PENINGKATAN KETERAMPILAN MENYIMAK TEKS NARASI BERBAHASA JAWA MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (Universitas Negeri Semarang, 2015)
Tujuan penelitian ini adalah meningkatkan keterampilan menyimak teks narasi berbahasa Jawa melalui model pembelajaran Think Pair Share pada siswa kelas IV SDN Ngaliyan 01 Semarang. Penelitian ini dilaksanakan 2 siklus, setiap siklus 2 pertemuan. Hasil penelitian menunjukkan; (1) keterampilan guru siklus I pertemuan 1 skor 25 (cukup), siklus I pertemuan 2 skor 31 (baik), siklus II pertemuan I skor 33 (baik), siklus II pertemuan 2 skor 36 (sangat baik), (2) aktifitas siswa siklus I pertemuan 1 skor 20,5 (cukup), siklus I pertemuan 2 skor 22,63 (baik), siklus II pertemuan 1 skor 23,35 (baik), siklus II pertemuan 2 skor 26,97 (sangat baik), (3) keterampilan menyimak siswa siklus I pertemuan 1 skor 60 (cukup), siklus I pertemuan 2 skor 68,2 (baik), siklus II pertemuan 1 skor 71,21 (baik), siklus II pertemuan 2 skor 75,6 (sangat baik). Simpulan dalam penelitian ini adalah melalui model pembelajaran Think Pair Share dapat meningkatkan keterampilan menyimak teks narasi berbahasa Jawa.Â The aim of this research is to improve the listening skill on Javanese narration text though Think Pair Share learning model towards 4th graders at SDN Ngaliyan 01 Semarang. This investigation was done in two cycles in which each cycle consists of two meetings. The results of the study showed that (1) the teacher skill in the first cycle at the first meeting obtained the score of 25 (fair) while at the second meeting gained the score of 31 (good) and in the second cycle gained the score of 33 (good) while at the second meeting gained the score of 36 (very good) (2) students activities in the first cycle at the first meeting obtained the score of 20,5 (fair) while at the second meeting gained the score of 22,63 (good) and in the scond cycle gained the score of 23,35 (good) while at the second meeting gained the scoreof 23,35 (good) while at the second meeting gained thr score of 26,97 (very good) (3) the students listerning skill imporved in the first cycle at the first meeting obtained the score of 60 (fair) while at the second meeting gained the score of 68,2 (good) and in the second cycle gained the score of 71,21 (good) while at the second meeting gained the score of 75,6 (very good). The study concluded that the Think Pair Share learning model could improve the listerning skill on Javanese narration text.